STABILITAS ANTOSIANIN DAN AKTIVITAS ANTIOKSIDAN TEPUNG BERAS HITAM BERDASARKAN JENIS KEMASAN DAN LAMA PENYIMPANAN - Nur Latifa; nurhidajah Nurhidajah; Muh yusuf (Jurnal Pangan dan Gizi, 2019)
Black rice flour during storage has the disadvantage of reducing the antioxidant content and antioxidants present in black rice flour due to improper packaging for storage so that the pH increases, the color will disappear so that the anthocyanin content will also decrease during storage. This study aims to determine the influence of packaging type and storage time to levels of anthocyanins, antioxidant activity, moisture content, and color of black rice flour. This research uses a factorial completely randomized design consisting of 2 factors: first factor type of packaging (PP and Alufo) with each thickness of 0.5 mm and second factor storage duration (0 days, 14 days, 28 days, 42 days, and 56 days) in room temperature. The results of statistical test showed that the type of packaging and storage duration influenced the anthocyanin content, antioxidant activity, moisture content, and color. Antosianin content of black rice flour at the end of shelf life on PP packaging of 5.39 ppm sample and Alufo 14.14 ppm sample. Antioxidant activity at end of shelf life in packing of PP equal to 18,6% and Alufo 24,48%. Water content at end of shelf life on packing PP 2,34% and Alufo 2,65%. The color is at the end of shelf life on the packaging of PP 8,351 and Alufo 7,568.